SOSIALISASI DAN EDUKASI AKAD SYARIAH UNTUK MENINGKATKAN PEMAHAMAN PESERTA EKSTRAKURIKULER PMR SMK KARYA WIJAYA KUSUMA - Siska Ariyanti; Zahra Nur Azizah, Lulu Rahmawati, Putri Jamilah, Surti Suti Ludiyawati, Nanda Vinolia Pratama, Devi (CV. ADIBA AISHA AMIRA, 2026)
This study aims to describe the improvement in the understanding of participants in the Wijaya Kusuma Vocational School Youth Red Cross extracurricular programme regarding sharia contracts through community service activities based on material presentation, discussion, and pretest–posttest evaluation. The subjects of the activity were 15 tenth-grade students who were partners in the sharia contract socialisation and education programme at the vocational school. Sharia contracts are positioned as agreements between two or more parties based on sharia principles, avoiding usury, gharar, and harmful practices. The implementation method included the delivery of material on the basics of sharia economics, types of contracts, and examples of their application, followed by interactive discussions and multiple-choice tests before and after the activity. The results show an increase in the average score from the medium-high category in the pretest to a higher category in the posttest, with several indicators such as understanding mudharabah, gharar, and halal transactions showing an improvement in the percentage of correct answers. These findings indicate that a communicative and structured learning approach is effective in strengthening Islamic contract literacy among vocational high school students.